MANAGING THE PROCESS OF SELF-ORGANIZATION OF THE PEDAGOGICAL COLLECTIVE AT A SUPPLEMENTARY EDUCATION ESTABLISHMENT FOR CHILDREN (Revista Inclusiones, 2020)
The research topicality is due to the inconsistency of organizational and personal goals and values of pedagogical staff at institutions of supplementary education for children. This inconsistency, on the one hand, negatively influences the image of an institution, decreases its potential for innovations, and impedes development strategies and the quality of functioning in general. On the other hand, it serves as a source of creativity, non-standard structures, and openness of the institution for varied demands and social groups interested in supplementary education for children. The article presents an approach to managing the process of self-organization of the pedagogical collective at a supplementary education establishment for children. Taking into account the ongoing discussions and recurrent debates, special attention is paid to interpretation of the “self-organization” notion. A pedagogical collective is viewed not as an object of management, but as a procedural phenomenon which should be not only guided towards cooperative activity but also maintain its orientation towards self-development, integrity, and responsibility.